Insights into Dyspareunia: From Diagnosis to Multimodal Treatment Approaches - Kołodziej, Klaudia; Mańdziuk, Dominika; Niewinna, Patrycja; Zaroda, Przemysław; Dąda, Paweł; Pawlik, Paweł; Kołodziej, Wojciech; Żuchowski, Michał; Wawrzkowicz, Jakub; Korga, Monika (Quality in Sport, 2024)
Introduction and Purpose: Dyspareunia is a sexual disorder associated with pain in women. It refers to pain related to sexual intercourse. Pain can occur during penetration attempts, during penetration, during intercourse, and shortly after penetration. Studies conducted in the United States indicate that the problem of pain during intercourse affects as much as 10-20% of women. [1] In Poland, this number is estimated to be around 13%.[1] The aim of this review is to delve into the existing literature on the diagnosis of dyspareunia in women and to raise awareness of its extensive nature, emphasizing an interdisciplinary approach to patient care. A Brief Description of the State of Knowledge: The etiology of dyspareunia is multifactorial and may arise from pathological changes in the vulva and vagina, inflammatory changes, contact irritations, as well as vulvar conditions such as lichen sclerosus and flat. [3] Additionally, hormonal changes, pelvic floor injuries, postpartum gynecological procedures also play a significant role. Psychological factors such as trauma, anxiety, and depression are also important [4]. Conclusions: Dyspareunia is a condition that significantly affects the quality of life of women in various ways, thus necessitating effective therapeutic approaches. Collaboration among diverse specialists such as gynecologists, sexologists, psychotherapists, psychiatrists, and physiotherapists is crucial. Further research focusing on multimodal strategies is needed to effectively tailor treatments and mitigate the systemic effects of chronic pain.